Pendidikan Sebagai Akses Penyelesaian Problematik Generasi NU Dalam Mempertahankan Keautentikan Tradisi Di Era Distrupsi - Firdaus, Agus Maulana; Habibi, M. Arja (DAS Institute, 2024)
The phenomena of secularization, liberalization of values, and shifts in local culture pose serious challenges to the sustainability and authenticity of Nahdlatul Ulama (NU) traditions. Secularization has led to a separation between religious values ​​and social and cultural life. Consequently, religious practices, often steeped in spiritual meaning, are often deemed irrelevant to modern life. Therefore, concrete steps are needed to bridge this gap. This research seeks to unravel the problem and find solutions. Therefore, this study is a library research study, seeking relevant research using primary and secondary data, including books, articles, and opinions from prominent figures, and analyzing them using discourse analysis techniques. This study concludes that for education to play a more effective role in maintaining the authenticity of NU traditions, policies are needed that support the strengthening of education based on local traditions and Aswaja values ​​within NU.